Future directions for monitoring and human health research for the Arctic Monitoring and Assessment Programme. Issue 1 (1st January 2018) - Adlard, B.; Donaldson, S. G.; Odland, J.O.; Weihe, P.; Berner, J.; Carlsen, A.; Bonefeld-Jorgensen, E. C.; Dudarev, A. A.; Gibson, J.C.; Krümmel, E.M.; Olafsdottir, K.; Abass, K.; et al.
ABSTRACT: For the last two and a half decades, a network of human health experts under the Arctic Monitoring and Assessment Program (AMAP) has produced several human health assessment reports. These reports have provided a base of scientific knowledge regarding environmental contaminants and their impact on human health in the Arctic. These reports provide scientific information and policy-relevant recommendations to Arctic governments. They also support international agreements such as the Stockholm Convention on Persistent Organic Pollutants (POPs) and the Minamata Convention on Mercury. Key topics discussed in this paper regarding future human health research in the circumpolar Arctic are continued contaminant biomonitoring, health effects research and risk communication. The objective of this paper is to describe knowledge gaps and future priorities for these fields.